Regional, Racial, and Mortality Disparities Associated With Neurosurgeon Staffing at Level I Trauma Centers. Issue 12 (December 2021) - Homo, Richelle L.; Grigorian, Areg; Chen, Jefferson; Figueroa, Cesar; Chin, Theresa; Kuza, Catherine M.; Lekawa, Michael; Nahmias, Jeffry
Background: Traumatic brain injury (TBI) occurs in approximately 30% of trauma patients. Because neurosurgeons hold expertise in treating TBI, increased neurosurgical staffing may improve patient outcomes. We hypothesized that TBI patients treated at level I trauma centers (L1TCs) with ≥3 neurosurgeons have a decreased risk of mortality vs. those treated at L1TCs with <3 neurosurgeons. Methods: The Trauma Quality Improvement Program database (2010-2016) was queried for patients ≥18 years with TBI. Patient characteristics and mortality were compared between ≥3 and <3 neurosurgeon-staffed L1TCs. A multivariable logistic regression analysis was used to identify risk factors associated with mortality. Results: Traumatic brain injury occurred in 243 438 patients with 5188 (2%) presenting to L1TCs with <3 neurosurgeons and 238 250 (98%) to L1TCs with ≥3 neurosurgeons. Median injury severity score (ISS) was similar between both groups (17, P = .09). There were more Black (37% vs. 12%, P < .001) and Hispanic (18% vs. 12%, P < .001) patients in the <3 neurosurgeon group. Nearly 60% of L1TCs with <3 neurosurgeons are found in the South. Mortality was higher in the <3 vs. the ≥3 group (12% vs. 10%, P < .001). Patients treated in the <3 neurosurgeon group had a higher risk for mortality than those treated in the ≥3 neurosurgeon group (odds ratio (OR) 1.13, 95% confidence intervals (CI) 1.01-1.26, P = .028). Discussion: There exists a significant racial disparity in access to neurosurgeon staffing with additional disparities in outcomes based on staffing. Future efforts are needed to improve this chasm of care that exists for trauma patients of color.